The Development of Performing Arts to Promote Local Identity in Supporting Tourists in Pathum Thani Province - Ngerndang, Artitaya; Rittibul, Pravit; Inthachote , Suchira; Boonsong, Panurat (Journal of Ecohumanism, 2025)
This research aimed to: 1) explore the identity of local arts and culture in Pathum Thani Province, and 2) develop performing arts based on local identity to support tourism in the region. Employing qualitative research methods, the study utilized document analysis, media reviews, field surveys, structured interviews, and data triangulation. The findings were synthesized to inform the design of performing arts, later presented as creative concepts by students in the course 07201005 Community Arts Innovation. The study revealed that Pathum Thani Province’s cultural identity is shaped by its ethnic diversity, resulting in a multicultural society. Its geography, defined by rivers and canals, serves as a center for activities, with agriculture playing a key role alongside industrial development that impacts the national economy. Pathum Thani balances sustainable development with a blend of traditional and modern lifestyles, preserving its uniqueness while embracing progress. These characteristics provide a rich foundation for creating performing arts that promote tourism. The study identified two key aspects for performing arts development: Creative dance reflecting local careers and wisdom and Creative dance rooted in traditions and beliefs. The creative dance concept highlights the knowledge and cultural heritage of the province’s seven districts, showcasing their unique identities and values through performance. Eight critical elements of dance creation were defined: 1) performance design, 2) performer selection, 3) choreography design, 4) performance prop design, 5) sound and music design, 6) costume design, 7) performance space design, and 8) lighting design. These elements integrate cultural identity with interdisciplinary knowledge, forming a guideline for innovative dance development. The research contributes to understanding the role of performing arts in cultural promotion and tourism while offering a foundation for future advancements in performing arts.